Transnational legal ordering of criminal justice / edited by Gregory Shaffer, Ely Aaronson. - Shaffer, Gregory C., 1958-; Aaronson, Ely, 1973- (Cambridge studies in law and society., 2020)
Hard and soft law developed by international and regional organizations, transgovernmental networks, and international courts increasingly shape rules, procedures, and practices governing criminalization, policing, prosecution, and punishment. This dynamic calls into question traditional approaches that study criminal justice from a predominantly national perspective, or that dichotomize the study of international from national criminal law. Building on socio-legal theories of transnational legal ordering, this book develops a new approach for studying the interaction between international and domestic criminal law and practice. Distinguished scholars from different disciplines apply this approach in ten case studies of transnational legal ordering that address transnational crimes such as money laundering, corruption, and human trafficking, international crimes such as mass atrocities, and human rights abuses in law enforcement. The book provides a comprehensive treatment of the changing transnational nature of criminal justice policymaking and practice in today's globalized world.